The natural history of multiple sclerosis: a geographically based study: 8: familial multiple sclerosis. - Ebers, G; Koopman, W; Hader, W; Sadovnick, A; Kremenchutzky, M; Mandalfino, P; Wingerchuk, D; Baskerville, J; Rice, G (2000)
We have examined the demographics and long-term outcome of 1044 patients with sporadic and familial multiple sclerosis in a population-based cohort from London, Ontario. The mean follow-up was 25 years in duration, and by this time most patients had reached the unambiguous endpoint scores of the Kurtzke disability status scale (DSS), DSS 6, 8 or 10. An affected family member was identified in 19.8% of the total population, and this subgroup was further divided arbitrarily into the following three groups by the type and number of relatives affected: (i) first degree only; (ii) first degree plus others; (iii) second or third degree. The outcome in these groups was compared with that for those patients who, at a mean 25 year follow-up, had no relatives known to be affected. Familial cases closely resembled those remaining sporadic in both demographics and outcome, although onset in the most heavily loaded families was earlier and male/female ratio was greater. The times to DSS 6, 8 and 10 did not differ significantly when sporadic, familial and familial subgroups were compared. These results provide no clinical support for viewing familial multiple sclerosis as distinct from the sporadic form. The observed recurrence rate for siblings in a strictly defined epidemiological sample was 3.5%, much as projected. These results validate the recurrence risks which have previously been derived from age-corrected data for these first-degree relatives.